P12. Comparison between impact echo test results and radiation survey of the primary barrier of a radiotherapy bunker. (September 2016) - Moosa, F.; Burger, H.; Fourie, H.; Trauernicht, C.; Blassoples, G.; Okwori, E.; Nyoni, B.; Moyo, P.
Abstract : Introduction: Groote Schuur Hospital constructed a new radiotherapy bunker for a high-energy linear accelerator. During construction areas of honeycombing became evident in the concrete. Honeycombing reduces the density of concrete and may affect the shielding integrity of the walls. Since the linac had not yet been installed, the radiation beam could not be used for testing, and an alternative non-destructive testing method had to be employed. The aim of this study is to compare the results from the impact echo testing with the radiation survey results. Materials and methods: In impact echo testing, a mechanical impact is used to create stress waves, which propagate through the concrete and are reflected or refracted where there are changes in material characteristics such as density. In theory, non-visible honeycombing at depth will present multiple reflection surfaces and should result in a broad-band response with multiple small peaks. The propagation of the stress wave is dependent on the elastic modulus, density and Poisson's ratio of the material. Radiation measurements at the same positions on the walls where impact echo testing was performed were done with the 6 MV linear accelerator during its safety survey, and the data was extrapolated for an 18 MV photon beam as per bunker design. Results: The impact echo results show that the density of the primary barrier ranged from 2.30 g/cc to 2.55 g/cc for the primary shielding wall adjacent to the maze (the other one is underground). The maximum measured dose rate from radiation survey on this wall was 0.5 μSv/h for a 6 MV beam, and calculated to be about 40 times higher for an 18 MV beam. An additional 40 cm of concrete shields the closest uncontrolled area. Conclusion: The radiation survey results are consistent with the results from the impact echo testing. No localized voids were found during the survey.